Distribution and conservation status of four endemic long-tailed macaque subspecies in Indonesia - ROBITHOTUL HUDA; RICHARD MOORE; WENDI PRAMESWARI; ITANG ITANG; ELISABET R.R.B. HUTABARAT; ISAI YUSIDARTA; UJANG WISNU BARATHA; DHENY MARDIONO; KARMELE LLANO SANCHEZ (Society for Indonesian Biodiversity, 2026)
Abstract. Huda R, Moore R, Prameswari W, Itang, Hutabarat ERRB, Yusidarta I, Baratha UW, Mardiono D, Sanchez KL. 2026. Distribution and conservation status of four endemic long-tailed macaque subspecies in Indonesia. Biodiversitas 27 (1): d270147. https://doi.org/10.13057/biodiv/d270147. Population data for island-endemic subspecies of the long-tailed macaque (Macaca fascicularis) remain scarce despite their Critically Endangered status. We conducted rapid grid-based surveys and community interviews (May-July 2023) on four Indonesian islands—Simeulue, Lasia, Maratua, and Karimunjawa—to estimate density, abundance, distribution, and anthropogenic pressures on Macaca fascicularis fusca, Macaca fascicularis lasiae, Macaca fascicularis tua, and Macaca fascicularis karimondjawae. Across all sites, we recorded 597 individuals in 51 groups, with mean density indices ranging from 0.79 individuals km⁻² on Simeulue (95% CI: 0.44-1.16) to 9.43 individuals km⁻² on Maratua (95% CI: 4.17-15.84). Macaques were strongly associated with forest-settlement and plantation edges, where interview data indicated frequent negative interactions and reliance on anthropogenic food sources. These results reaffirm the Critically Endangered status of three subspecies under IUCN Criterion D and indicate a possible Criterion A2 decline for M. f. fusca, underscoring the need for targeted coexistence measures, habitat protection, and structured monitoring.